Exploring the impact of innovative developments to the installation process for an offshore wind farm. (15th November 2015) - Barlow, Euan; Tezcaner Öztürk, Diclehan; Revie, Matthew; Boulougouris, Evangelos; Day, Alexander H.; Akartunalı, Kerem
Abstract: For offshore wind to be competitive with mature energy industries, cost efficiencies must be improved throughout the lifetime of an offshore wind farm (OWF). With expensive equipment hire spanning several years, installation is an area where large savings can potentially be made. Installation operations are subject to uncertain weather conditions, with more extreme conditions as OWF developments tend towards larger sites, further offshore in deeper waters. One approach to reduce the cost of the installation process is to evaluate advanced technologies or operational practices. However, in order to demonstrate cost savings, the impact of these advances on the installation process must be quantified in the presence of uncertain environmental conditions. To addresses this challenge a simulation tool is developed to model the logistics of the installation process and to identify the vessels and operations most sensitive to weather delays. These operations are explored to identify the impact of technological or operational advances with respect to weather delays and the resulting installation duration under different levels of weather severity. The tool identifies that loading operations contribute significantly to the overall delay of the installation process, and that a non-linear relationship exists between vessel operational limits and the duration of installation. Highlights: A simulation model evaluates innovations to the installation of offshore wind farms. Investment in advanced technologies or vessels can therefore be justified. The impact of operational limits and vessel characteristics are quantified. A case study illustrates time reductions achieved through technological advances.